Working outside the lines: A case for knowledge exchange in the academic library. Issue 2 (1st June 2020) - Barlow, Amy; Bocko, Amy
Abstract: This article presents a case for the benefits of knowledge exchange in the academic library. The authors define knowledge exchange and use the concept as a framework for describing a peer learning experience rooted in best digital practices education. Their partnership enabled the authors to extend their professional roles while developing innovative services for library users. The authors distill their unique experience into a set of actionable recommendations.